PENGEMBANGAN LEMBAR KERJA SISWA (LKS) POKOK BAHASAN PERBANDINGAN UNTUK SMP KELAS VII BERSTANDAR NCTM (NATIONAL COUNCIL OF TEACHERS OF MATHEMATICS) - Hardy, Agustya; Suharto, S; Trapsilasiwi, Dinawati (Department of Mathematics Education , University of Jember, 2014)
Abstract. The research aimed to know the process and result of development of student worksheetson NCTM’s standartforcomparison topic at seven grade of junior high school. Student worksheetsdevelopment model refers to 4D Thiagarajan models which has 4 steps namely define, design, develop, and disseminate. This research has aproductof student worksheets thatcontained fiveNCTMprocess standardsbywhichproblem solving, reasoningandproof, communication, connections, andrepresentation. Based on validation process and tryout, it can be concluded that the student worksheets had fullfiled with validity, practice, and effective criteria. Key Words: 4D Thiagarajan models, student worksheet, NCTM process standards, comparison